2011
DOI: 10.26719/2011.17.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Needlestick injuries among health care workers of University of Alexandria hospitals

Abstract: The aims of this cross-sectional study were to investigate the prevalence and circumstances of needlestick injury (NSI) among heath care workers at University of Alexandria teaching hospitals and to assess the effectiveness of the existing control measures and standard precautions. Data were obtained by anonymous, self-reporting questionnaire from 645 nurses, physicians and ancillary staff in 2007. Around two-thirds of workers (67.9%) had suffered at least 1 NSI in the last 12 months. High-risk patients (with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
58
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 10 publications
18
58
5
Order By: Relevance
“…9,21 our study estimated that 80.6% of HCWs experienced needle stick accidents at least once which is in agreement with other studies conducted in alexandria, Egypt, 22 South africa 23 and Indonesia 9 as 67.9%, 91% and 77% respectively of HCWs reported sustaining needle stick accident. Lower prevalence of NSIs was reported among HCWs in two Malaysian teaching hospitals (31.6% and 52.9% respectively).…”
supporting
confidence: 81%
“…9,21 our study estimated that 80.6% of HCWs experienced needle stick accidents at least once which is in agreement with other studies conducted in alexandria, Egypt, 22 South africa 23 and Indonesia 9 as 67.9%, 91% and 77% respectively of HCWs reported sustaining needle stick accident. Lower prevalence of NSIs was reported among HCWs in two Malaysian teaching hospitals (31.6% and 52.9% respectively).…”
supporting
confidence: 81%
“…79.5% and 80.1% respectively when compared to the present study findings. The studies from Alexandria hospital [16] Egypt (67.9%), a study from Nigeria [17] involving primary health care workers (57.1%) and a study from Pakistan [18] involving health care workers of two tertiary care hospitals comprising both public and private health sector (64%) have shown marginally lower percentage of needle stick injuries in relation to the present study observation. In contrast to the present study findings, studies from Germany [3,19] Maharashtra-India [13] and Mongolia [20,21] have shown significant lower proportion of needle stick injuries i.e.…”
Section: Discussionmentioning
confidence: 56%
“…The most common belief is that; as the work experience increases chances of exposure to needle stick injuries will come down as supported by the study done at Egypt and Malaysia [16,22]. Whereas a study from Pakistan [18] involving health care workers of two tertiary care hospitals has shown the results similar to the present study where it was observed that the odds of having needle stick injuries were higher among health care workers who were practicing for more than five years which was found to be statistically significant.…”
Section: Discussionmentioning
confidence: 87%
“…[34] On other hand, the results of this study revealed that the negative attitude of the nursing students in opining that reporting after NSI was not useful, reflect a lack of understanding of the dangers of non-reporting and possible spread of infection. In a study by Hanafi et al (2011), it recognized that the normal explanation behind unreported NSIs warranted consideration since there is minimal advantage, particularly when reporting can bring about employment problems or other adverse issues. [35] Obstructions to reporting ought to be suitably distinguished and disposed of with a specific end goal to guaranteeing guidance and education of students after presentation.…”
Section: Perception Of Students On Needle Stick Injurymentioning
confidence: 99%